The issue of argentine musical nationalism (Revista del Instituto de Investigación Musicológica "Carlos Vega", 2017)
Firstly, this review paper approaches the issue of nationalism in music and the argentine musical movement call Nationalism. It presents the ideas of “nation” and “nationalism” and their naturalistic and deterministic conceptions. Then, it develops the historical and socio-political circumstances of the Argentine nationalism. The concept of “musical nationalism” is elaborated based on the Dalhausian and topic theories, to then circumscribe it to the Argentine context based on the analysis of two key works: Alberto Williams’ piano piece El rancho abandonado and Arturo Berutti`s opera Pampa. Finally, it lists the historical factors and musical characteristics of the Argentine nationalism.
Keywords: nationalism; musical nationalism; theories; Argentina